Linking Training, Work Motivation, And Job Satisfaction To Employee Performance Through Work Engagement - Robe, Elsita Delima; Lindiawati; Emma Yulianti (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
Employee performance is a key factor in organizational success. This study aims to examine the effects of training, work motivation, and job satisfaction on employee performance, mediated by work engagement, at LPP TVRI Nusa Tenggara Timur. The research adopts a quantitative, explanatory approach using a sample of 73 employees selected through non-probability sampling. Data were collected via questionnaires and analyzed using Partial Least Squares (PLS) with War PLS software. The results reveal that training, work motivation, and job satisfaction have significant positive impacts on employee performance. Moreover, work engagement significantly mediates the relationship between training and employee performance. These findings highlight the importance of improving employee competencies and creating an engaging work environment to enhance organizational performance.